EVALUATION STUDY OF EUCHEUMA COTTONII SPECIES OF SEAWEED CULTIVATION BASED ON OCEANOGRAPHIC PARAMETERS IN PASIEA, BONEGUNU SUBDISTRICT, NORTH BUTON DISTRICT - Salihin, Abdilah; Muhiddin, Amir Hamzah; Yasir, Inayah (Jurnal Ilmu Kelautan SPERMONDE, 2019)
This study aims to determine the level of land suitability and the area of Eucheuma cottonii in Pasiea waters, to know the dynamics and correlation of oceanographic parameters towards the growth of E. cottonii seaweed. This research was conducted in August-October 2018 in the area of seaweed cultivation in Pasiea waters. The observation station consisted of six stations located in the area of seaweed cultivation. Oceanographic parameters dynamics were measured by oceanographic parameters measured which significantly affected the growth of seaweed species E. cottonii in the form of temperature, salinity, brightness, depth of flow, current velocity, nitrate, and phosphate has been mentioned before which wasthen overlaid on the map maker application to produce a map of the suitability level of E. cottonii seaweed cultivation in Pasiea waters. The results of the spatial analysis showed that the level of Pasiea waters suitability based on oceanographic parameters was in the less suitable category covering 1410 ha and did not match 1 Ha, whereas based on the daily growth rate of E. cottonii the overall research locations were in the excellent category of 1411 ha. The dynamics of oceanographic parameters were still within the range that can be tolerated for the growth of E. cottonii with parameters that correlate to the daily growth rate of salinity, brightness, phosphate, and nitrate.